(untitled) (Vietnam Journal of Community Medicine, 2026)
Objective: The study was conducted to evaluate patient satisfaction with medical services quality at Vinmec Phu Quoc International General Hospital. Methods: A cross-sectional descriptive study was conducted on 243 outpatients at Vinmec Phu Quoc International General Hospital from January to February 2024, using a questionnaire based on the modified SERVPERF scale. Results: Correlation analysis showed a positive and statistically significant relationship between service quality factors and patient satisfaction. Specifically, Tangibles & Assurance had the strongest correlation with satisfaction (r = 0.798, p < 0.001), followed by Responsiveness & Empathy (r = 0.753, p < 0.001), and finally Reliability (r = 0.592, p < 0.001). Multiple regression analysis showed that all service quality factors had a positive and statistically significant effect on patient satisfaction: (1) Tangibles & Assurance had the strongest effect (β = 0.510, p < 0.001); (2) Responsiveness & Empathy had a significant effect (β = 0.267, p < 0.001); (3) and Reliability also had an effect (β = 0.114, p < 0.05). Conclusion: Improving the quality of medical services, especially in terms of facilities and service attitude, is an important solution to improve patient satisfaction. The study suggests that the scope and methods should be expanded in future studies.